Transpedicular Approach for Subaxial Cervical Spine - Sharma, Krishna (Nepal Journal of Neuroscience, 2016)
Cervical spine decompression, fusion and fixation are required when pathologies like trauma, degeneration, infection or tumor destabilizes the spine or cause compression on neurovascular structures. Many approaches and instrumentation technique have evolved to achieve a stable spine closest to its natural state, preserving the anatomy and the function. Transpedicular approach to cervical spine has been a new addition to the attempt. Here, our experience of the procedure is presented. Total of 38 cases underwent this procedure from 2014 February to 2015 December. Twenty-four cases had unstable spine due to trauma, twelve had severe multilevel spondylotic cord compression and two had dump bell schwannomas. Their age ranged from 24 to 76 years with 22 males and 16 females. The procedures were done under general anesthesia in prone position on Gardner-Wells pins and a horseshoe headrest. After exposing the pedicles, 3.5 mm by 22 mm titanium poly-axial screws where inserted through the pedicles using the technique described by Professor Abumi. The pedicle screws were connected by a connecting rod, which had been bent in accordance with the normal cervical lordosis. Fusion was done using the bones obtained from the spinous process and laminae. There were fifty-six screws which were mis-directed, and had to be immediately corrected. There was no incidence of significant pedicle penetration or injury to neuro-vascular structures. There was temporary weakness of upper limbs postoperatively in seven patients, which recovered fully in two months’ time. There were six deaths due to uncontrolled septicaemia triggered by chest infection. The rest of the patients were discharged between one to six weeks after surgery. Transpedicular fixation of unstable cervical spine provides biomechanically a very rigid and good correction of sagittal alignment with a high-fusion rate and a few surgical complications. After realizing these advantages, transpedicular screw fixation in cervical spine is becoming an increasingly popular spine surgeon’s armamentarium. Nepal Journal of Neuroscience 13:11-18, 2016